Engagement analysis on buzzer information transactions: Questioning the impression of Indonesian talk show program and how Netizen response on Twitter - Kamil, Sitti Utami Rezkiawaty; Saidin, Saidin; Sultan, M. Iqbal; Mustamin, Masita; Lestari, Indra; Erif, La Ode Muhammad; Tandiayu', Desderia Cindy; Badaruddin, Ahmad (Technium Social Sciences Journal, 2022)
The social media phenomenon increasingly widespread and uses as a references news, information and knowledge. The development of social media also gave birth to many phenomena including the emergence of a phenomenon called buzzer. Twitter as an identical media uses buzzer activities because it has a grand gait on enlivening dialogue and as trendingtopic, a news categorize according to key terms or exclusive topics through fence syndication (#) to move social media users.This research related to the tendency of content exchanged buzzer and followers. The research results are presented in the form of descriptive qualitative research, which aims to describe the character of the message contained in the information exchanged by the buzzer. The samples used in this study were 15 tweets about #ILCPanggungProvokasi and 13 tweets about #StopAcaraILC.This study does not prioritize the size or sampling. If the data collected is in-depth and can explain the phenomenon being studied, there is no need to look for other sampling. The emphasis here is on the problem of depth (quality) of data, not quantity of data. The research period focuses on buzzer content in the period from February 18 to February 20, 2020, which is a trending topic and is discussed openly by the public, giving rise to a certain understanding that is widespread. The Result of this reaserch show that The interaction of buzzer information on Twitter social media is a deliberate relationship because of the formation of manipulated content in political discourse through the hashtag #ILCPanggungProvokasi as an early advocate of discourse. The buzzer then creates a counter-discourse via #StopAcaraILC, which is offensive in nature with agitative and monotonous discourse.transactions on Twitter social media as an activity are not of high quality but are able to attract attention and are widely responded to by the public.